2022
DOI: 10.3389/fped.2022.935951
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal B-Cell Maturation and Increased Transitional B Cells in CBL Syndrome

Abstract: CBL syndrome is a Noonan-like RASopathy with heterogeneous clinical phenotype and predisposition to juvenile myelomonocytic leukemia (JMML). Here we describe two patients with identical germline CBL mutation and clinical and immune-hematological overlapping features with autoimmune lymphoproliferative syndrome (ALPS) and B-cell expansion with NF-κB and T-cell anergy (BENTA) syndrome. Increased immature/transitional B cells can be depicted in CBL syndrome, ALPS, and BENTA. Nonetheless, our patients here describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…By functioning as an adaptor, CBL has also been reported to act as a positive regulator of signaling elicited by RTKs. Extensive studies demonstrated that E3 activation is required for RTKs ubiquitination (Martinelli et al, 2012;Niemeyer et al, 2010;Saettini et al, 2022;Thien et al, 2001). Multiple lines of evidence support the view that RASopathy-and leukemia-associated CBL syndrome is a highly variable condition accounting for <1% of subjects with some clinical features reminiscent of NS (Martinelli et al, 2010(Martinelli et al, , 2015Niemeyer et al, 2010;Pérez et al, 2010).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…By functioning as an adaptor, CBL has also been reported to act as a positive regulator of signaling elicited by RTKs. Extensive studies demonstrated that E3 activation is required for RTKs ubiquitination (Martinelli et al, 2012;Niemeyer et al, 2010;Saettini et al, 2022;Thien et al, 2001). Multiple lines of evidence support the view that RASopathy-and leukemia-associated CBL syndrome is a highly variable condition accounting for <1% of subjects with some clinical features reminiscent of NS (Martinelli et al, 2010(Martinelli et al, , 2015Niemeyer et al, 2010;Pérez et al, 2010).…”
Section: Discussionmentioning
confidence: 92%
“…By functioning as an adaptor, CBL has also been reported to act as a positive regulator of signaling elicited by RTKs. Extensive studies demonstrated that E3 activation is required for RTKs ubiquitination (Martinelli et al, 2012; Niemeyer et al, 2010; Saettini et al, 2022; Thien et al, 2001). Multiple lines of evidence support the view that RASopathy‐ and leukemia‐associated mutations affect CBL function and RTKs ubiquitination by impairing the E3 catalytic activity of the protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation